2021
DOI: 10.1002/ase.2126
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy education for medical students in the United Kingdom and Republic of Ireland in 2019: A 20‐year follow‐up

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 105 publications
0
32
0
1
Order By: Relevance
“…In the United Kingdom and Ireland, 10,093 students study medicine (Smith et al, 2022), the number of students is controlled by the Medical Workforce Standing Advisory Committee (1997). It is not just medical students who use human body donors in the United Kingdom and Ireland; the majority of institutions also teach a wide variety of allied health care professionals and deliver a range of higher surgical training programs.…”
Section: The United Kingdom and Ireland Body Donation Contextmentioning
confidence: 99%
“…In the United Kingdom and Ireland, 10,093 students study medicine (Smith et al, 2022), the number of students is controlled by the Medical Workforce Standing Advisory Committee (1997). It is not just medical students who use human body donors in the United Kingdom and Ireland; the majority of institutions also teach a wide variety of allied health care professionals and deliver a range of higher surgical training programs.…”
Section: The United Kingdom and Ireland Body Donation Contextmentioning
confidence: 99%
“…One area that has been slow to embrace technological advances has been anatomy, a field that is of critical importance to medicine and the delivery of health care. Today, in most medical schools, anatomy is taught in the traditional fashion with cadavers [ 9 - 11 ], and only a few leading medical schools are venturing into the domain of digital anatomy, where the technologies of the Internet of Things, especially VR, AR, and MR, are used to recreate human structures to support the study of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, anatomy educators put more emphasis on the adoption of new technologies, team-based learning, strengthening interdisciplinary education, and simplifying pre-clinical courses [6]. Many countries had similar trend in the United States, such as the United Kingdom, Africa, the Middle East and China [18,19]. A national survey of a ve-year clinical medicine project in China found that the total course time of anatomy course had been reduced by 11% over three decades.…”
Section: Discussionmentioning
confidence: 99%